Cytotoxic triterpene saponins from Cercodemas anceps. Issue 16 (15th August 2015) - Cuong, Nguyen Xuan; Vien, Le Thi; Hanh, Tran Thi Hong; Thao, Nguyen Phuong; Thao, Do Thi; Thanh, Nguyen Van; Nam, Nguyen Hoai; Thung, Do Cong; Kiem, Phan Van; Minh, Chau Van
Graphical abstract